The role of a training intervention in reducing email overload and improving productivity - Campbell, Kerry Meghan (My University, 2017)
Emails have become a fundamental computer application and business tool, in organisations across the global. This is because of the accessibility and convenience of emails which have generated an array of benefits to both employees and their organisations. However, this accessibility has led to an over-reliance on emails, which often has the negative consequence of email overload. Email overload continues to be a recurring issues experienced by employees universally, which research has found to have negative implications on employees’ wellbeing and productivity. Yet there has been limited research, particularly in South Africa, that aims to reduce email overload among employees. Thus, this research report investigated how the role of providing employees with a job resource (training intervention) could increase perceived productivity and eliminate email overload and change caused by the job demands (emails) on employees .In order to examine this effect, this research utilised a pretest post-test control group design on order to compare the impact of a training intervention in reducing email overload and increasing productivity. The quantitative results revealed that the training intervention contributed to a decrease in feelings of email overload among the participants. Additionally, focus groups were administered to determine participants’ experience with emails both prior to the training and after the training, to gain a clearer understanding of the best practices used to eliminate email overload. These findings observed that the participants transferred learnt contents from training into their working lives. Thus research both further contributes to other research currently associated with email and email overload, and also provides a greater understanding of the need to provide employees with job resources much like training intervention in order to counteract those job demands like emails, that are often ignored.
A research report submitted to the Faculty of Humanities, School of Human and Community Development, in partial fulfilment of the requirements for the degree of Master of Arts by coursework and research report in the field of in Organisational Psychology, University of the Witwatersrand, Johannesburg September 2017
Keywords: Electronic mail messages--Management; Information resources management; Industrial productivity